Functional improvement by tendon transfer for residual wrist dysfunction after botulinum therapy for severe upper limb spasticity: a case report - Takatoshi Hara; Yuta Miyazaki; Daisuke Nishida; Naho Takahashi; Keiko Sone; Yuki Hara; Ayano Matsui; Masahiro Abo (Journal of Medical Case Reports)
Abstract Background Spasticity is a motor disorder characterized by a velocity-dependent increase in tonic stretch reflexes, and hyperactive tendon reflexes, often resulting from upper motor neuron syndrome. Prolonged untreated spasticity can lead to contractures, joint deformities, and pain, significantly impairing activities of daily living. We report a case where a stepwise treatment approach—combining repeated botulinum toxin A, occupational therapy, and tendon transfer surgery—led to significant functional improvement in a patient with severe upper limb spasticity and residual wrist contracture. Case presentation The patient was a 24-year-old Japanese man who underwent surgery for intractable epilepsy as a 7-year-old child and developed left upper limb paralysis after surgery. From the age of 22 years, spasticity worsened, and in addition, the range of motion of the wrist joints became markedly restricted, especially dorsiflexion. Botulinum toxin A therapy was planned and a total of four injections were administered to the left upper limb. Occupational therapy was used in conjunction with the treatment. These treatments reduced spasticity, improved Fugl–Meyer Assessment scores by 2 points, and slightly improved upper extremity function. However, because wrist dorsiflexion restriction remained, additional tendon transfer surgery was performed. This procedure improved his active dorsiflexion of the hand joint to 20°, and 8 weeks after surgery, his Fugl–Meyer Assessment score improved to 52 points. Eventually, the functional use of his left upper limb increased, and he was able to use it to help open and close bottle caps. Conclusions This case report demonstrates the successful application of a stepwise treatment approach, combining repetitive botulinum toxin A therapy, occupational therapy, and tendon transfer surgery, for severe upper limb spasticity with residual wrist joint impairments. These findings highlight the importance of tailoring treatment strategies to individual patient characteristics, particularly the presence of residual voluntary muscle activity and the absence of structural joint deformities. This case illustrates the critical role of tendon transfer surgery as a complementary intervention to overcome the limitations of conservative treatments, leading to substantial functional recovery. Future studies should aim to establish clear criteria for selecting candidates for tendon transfer surgery to ensure optimal functional outcomes for patients with severe spasticity.